Student Motivation in Cross-Disciplinary Bildung Education: Learnings from a Case Study in the Netherlands - Demeijer, Frederique; van der Velde, Robin; Labrie, Nanon; Zweekhorst, Marjolein (Teaching and Learning Inquiry, 2025)
There is a growing interest in cross-disciplinary education aimed at instilling an open mindset in students in order to help them navigate complex societal issues. Since this requires commitment to learning, self-reflection, and venturing out of the “known,” it is essential to understand student motivation for this type of learning that goes beyond traditional academic pursuits. This article explores first-year students’ motivation in the Broader Mind Course (BMC) at Vrije Universiteit Amsterdam (VU). By drawing on qualitative interview data (n=23) of all actors involved—students, teachers, course designers, and management—we explore what elements support or impede participation, using self-determination theory as a lens. The results show that a balance between organisational guidance and freedom of choice should be ensured (autonomy), traditional external incentives and scaffolding are needed (competence), and educators should create a secure atmosphere (relatedness). The results of this study provide useful insights for the development of innovative and engaging cross-disciplinary courses for students’ personal, social, and academic development.